2017
DOI: 10.1111/gfs.12328
|View full text |Cite
|
Sign up to set email alerts
|

Fresh and ensiled forage plants—total composition, silage losses and the prediction of silage composition from the crop

Abstract: Twenty ley and whole‐crop samples were analysed before and after ensiling to determine the proportion of dry matter (DM) that could be accounted for by the sum of 12 chemical assays for ash, ash‐excluded‐amylase‐treated neutral detergent fibre (aNDFom), starch, water‐soluble carbohydrates (WSC), pectin, crude protein (CP), CP in aNDFom (CPndf), ammonia, crude fat, phenolics, plant organic acids and liquid fermentation products (acids and alcohols). Crop components, utilized during silage fermentation and the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 34 publications
0
9
0
2
Order By: Relevance
“…The average in vivo organic matter digestibility of the grass silages was slightly lower than of the fresh grass. Udén () stated that factors affecting the prediction from fresh crop are effluent losses, aerobic deterioration, fermentation loss of sugars and true protein, and products formed such as acids and alcohols. He found that if effluent losses and oxygen ingress were prevented, values for most of the components can be almost completely transferred from fresh grass to the silage.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The average in vivo organic matter digestibility of the grass silages was slightly lower than of the fresh grass. Udén () stated that factors affecting the prediction from fresh crop are effluent losses, aerobic deterioration, fermentation loss of sugars and true protein, and products formed such as acids and alcohols. He found that if effluent losses and oxygen ingress were prevented, values for most of the components can be almost completely transferred from fresh grass to the silage.…”
Section: Resultsmentioning
confidence: 99%
“…Also, this allows for early feed planning and it is easier to sample the grass at ensiling (Pickert et al, ). Moreover, fewer samples may be needed than with conventional silo sampling (Udén, ).…”
Section: Introductionmentioning
confidence: 99%
“…There are very few data published on the composition of the non‐WSC proportion of the “rest fraction” in forages or on what the consequences that this fraction may have on diet formulations and ensiling properties. In a previous paper, Udén () found a mean plant OA level in eleven leys and nine whole crops (see Table S1) of 65 (51–98) and 44 (14–70) g/kg DM respectively. Pectin levels ranged from 39 to 175 (mean = 86), whereas levels of soluble phenolics were below 3 g/kg DM.…”
Section: Introductionmentioning
confidence: 88%
“…Plant material, sample preparation and analytical methods were described earlier (Udén, ) and are only presented here in brief. A total of eleven ley crops of timothy, red clover and white clover from two cuts and two maturities (late 1st‐cut red clover sample missing) and nine whole crops (WC) of barley, wheat and maize from three stages of maturity were used in this study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation